Box-Behnken Design for Optimization on Esterification of Free Fatty Acids in Waste Cooking Oil Using Modified Smectite Clay Catalyst - Buasri, Achanai; Lertnimit, Suthita; Nisapruksachart, Arnon; Khunkha, Issara; Loryuenyong, Vorrada (ASEAN Journal of Chemical Engineering, 2023)
A potential alternative fuel option is biodiesel, which is produced mostly from natural resources due to the limited availability of petroleum supplies and environmental issues. Waste cooking oil (WCO) containing a high concentration of free fatty acid (FFA) can be transformed into biodiesel, which substantially benefits the environment and for reducing the fuel . The use of smectite clay as a catalyst in the esterification reaction of WCO with methanol was studied. Smectite was chemically activated by sulfuric acid (H2SO4) to obtain the acid-modified smectite. The utilization of an acid-catalyzed esterification procedure as a pre-treatment for WCO for biodiesel synthesis has been studied in some detail. However, there aren’t many effective ways to optimize this operation. The process variables used in this study’s esterification of FFAs in WCO were optimized using a Box-Behnken design (BBD). At atmospheric pressure, the catalyst amount of 5.03 wt%, the methanol to WCO molar ratio of 22.38, and the reaction time of 3.01 h are the optimal running parameters for accomplishing 97.96% FFA conversion. The catalyst was employed five times in a row without noticeably lowering its catalytic effectiveness. The results showed that smectite clay is an essential, low-cost, and recyclable catalyst for the esterification of FFA in WCO.